Sir Abe Bailey : his life and achievements - Sayer, Hamilton (Department of Historical Studies, 2016)
On the suggestion that something be written on Abe Bailey, the first question to pass through my mind was, who on earth is Abe Bailey anyway? The name sounded reasonably familiar, and indeed is. For most people, the name 'Bailey' is associated with the Abe Bailey Institute of Inter-Racial .Studies (now called. 'Centre for Inter-Group Studies') and the Abe Bailey Bursary, the latter being a grant to help university students finance their studies. But, it is probably true to say that not much more is known about this man which in his own way, contributed so much to South Africa in such a variety of fields and who left behind him such a rich legacy for the country of his birth, South Africa. This research paper deals exclusively with the life and achievements of Sir Abe Bailey. As there is, to date, no official biography on him, the contents of this work have had to be gleaned from a wide variety of source material, ranging from Government and press publications on the one hand to personal interviews and private correspondence of contemporary figures on the other. Where possible, the information gained has been verified, but, inevitably, time has militated against a closer critique regarding the validity of some of the opinions expressed by other writers on the personality and impact of Bailey.